An examination of strategies employed by female protagonists to confront victimhood in domestic noir - Samarawickrama, Gajasinghe Hewatalagahage Isuru Enakshi (2023)
This research examines how the female protagonists of domestic noir shed their victimhood and regain their agency, exploring how the concepts of female victimhood, female violence and female agency are portrayed in domestic noir. As domestic noir is a relatively new subgenre that emerged in 2012, there is still little research to be found, especially in terms of female victimhood and the depiction of femininities and masculinities of its protagonists. This study analyses the heterosexual marriages in three domestic noir novels, Gone Girl by Gillian Flynn (2012), The Silent Wife by A. S. A. Harrison (2013) and The Girl on the Train by Paula Hawkins (2015), exploring how the four major aspects of inversion of normative feminine and masculine behaviour, gender performance and masquerade, female victimhood and agency, and the relationship between gender and violence are portrayed in these novels. In exploring these aspects, this research aims to identify whether the female protagonists of domestic noir actually subvert patriarchal gender norms and the norms of traditional crime fiction, if they successfully shed their victimhood and whether their victimhood and violence categorise them as heroines, anti-heroines or villainesses.